(3OQGSI eUQajI JMdjdjI eY edMb HGdaJGhi GdTQYjIs - (3eMehO MSf(B, (3UhGfs ((3YeGf(B:s (3OGQ hGFd ddfTQ hGdJhRjY(B,s, 2006)
(3fTCI GdeUGQa hJWhQgG(B- (3GdeUGQa GdeQcRjI(B- (3fTCI GdeUGQa GdESdGejI(B- (3GdehGQO GdeGdjI aj GdeUGQa GdESdGejI(B- (3GSJNOeGJ GdCehGd aj GdeUGQa GdESdGejI (B-(3Jcjja GdCYeGd GdeUQajI GdeJfhYI(B- (3GSJNOeGJ GdGehGd aj GdeUGQa GdESdGejI(B- (3GdQbGHI Ydi CfTWI GdeUGQa GdESdGejI(B- (3QbGHI GdHfc GdeQcRj(B- (3JMbjb GdCQHGM hJhRjYgG aj GdeUGQa GdESdGejI(B- (3QDjI eSJbHdjIs
Keywords: (3GdEbJUGO GdESdGejs; (3GdHfhcs; (3GdHfhc GdESdGejIs